The relationship between strategic approaches and academic procrastination in English learning among Chinese college students: the mediating effect of neuroticism - Zhou, Yan (Frontiers in Education, 2025)
Drawing on the perspectives of planned behavior theory and the triple A theory, this study aims to investigate the association between college students’ strategic approaches and academic procrastination in English learning, as well as the mediating effect of neuroticism. A total of 1,169 college students completed surveys including the Approaches and Study Skills Inventory for Students, NEO Five-Factor Inventory, and Aitken’s Procrastination Inventory. The findings revealed a significant inverse correlation between strategic approaches and both neuroticism and academic procrastination in English learning. Additionally, neuroticism exhibited a significant positive correlation with academic procrastination. Further analysis confirmed that neuroticism significantly mediated the association between strategic approaches and English learning procrastination, accounting for 12.25% of the total effect. The findings suggest that neuroticism operates as a plausible, though not definitive, mechanism linking strategic learning behaviors to procrastination.